The Role of Preschool Education Services on Parents Employment in Lithuania - Čižauskaitė, Aušra; Gruževskis, Boguslavas (Socialinė teorija, empirija, politika ir praktika, 2018)
[only abstract and keywords in English; full article, abstract and keywords in Lithuanian] The aim of the article is to investigate the effect of a preschool educational institutions role on the employment of parents, who have preschool-aged children in Lithuania. After completing a survey about the employment of Lithuanian families with preschool-aged children and preschool establishments, one main hypothesis is put forward, aimed at understanding what impact not attending preschool has on parents’ employment. A quantitative research method is used to investigate the hypothesis. It is based on statistical analysis of a 2014 European Union Survey of Income and Living Conditions (EU-SILC). With the help of descriptive statistics, logistic regressions and Chi-square tests, this research analyses what impact not attending preschool has on children parents’ employment. It can be argued that the hypothesis is confirmed as the research results show that not using preschool services has a different effect on mothers’ and fathers’ economic activity. Therefore not attending preschool establishments has a major negative effect on mothers’ employment status rather than fathers’. In terms of family policy typologies it can be seen that paid and unpaid work distribution in Lithuania is associated with traditional family policy model. In this case, the provision of public preschool services is not the main family policy instrument, since the priority in Lithuania is to provide a financial support through the promotion of childcare at home. Lithuanian mothers choose to participate in a relatively long parental leave system. All this implies the view that the limited availability of preschool services might limit possibilities for mothers to participate in the labour market due to the traditional family policy model existing in the country. Finally, results allow to assume that an accessibility of preschool establishments stimulates parents to work, however, it is not a crucial factor due to financial aspects. An important role is played by unpaid care of the children provided by relatives and friends. Therefore, it can be interpreted as a compensation for the lack of public preschool services for families wishing to successfully continue their participation in the labour market.